2011
DOI: 10.1534/genetics.110.121798
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli rnlA and rnlB Compose a Novel Toxin–Antitoxin System

Abstract: RNase LS was originally identified as a potential antagonist of bacteriophage T4 infection. When T4 dmd is defective, RNase LS activity rapidly increases after T4 infection and cleaves T4 mRNAs to antagonize T4 reproduction. Here we show that rnlA, a structural gene of RNase LS, encodes a novel toxin, and that rnlB (formally yfjO), located immediately downstream of rnlA, encodes an antitoxin against RnlA. Ectopic expression of RnlA caused inhibition of cell growth and rapid degradation of mRNAs in DrnlAB cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(171 citation statements)
references
References 41 publications
(58 reference statements)
3
163
0
Order By: Relevance
“…There are also known TA systems that use the two-component protease ClpP, which cooperates with the ATPase-active chaperones ClpA or ClpX (11,12). Moreover, degradation of the antidote can be carried out by more than one protease (12)(13)(14)(15). In contrast to the E. coli antitoxins, knowledge of the proteolysis of antitoxins from other bacterial species is scarce.…”
mentioning
confidence: 99%
“…There are also known TA systems that use the two-component protease ClpP, which cooperates with the ATPase-active chaperones ClpA or ClpX (11,12). Moreover, degradation of the antidote can be carried out by more than one protease (12)(13)(14)(15). In contrast to the E. coli antitoxins, knowledge of the proteolysis of antitoxins from other bacterial species is scarce.…”
mentioning
confidence: 99%
“…(MH1 araD + ) were used as wild types (Koga et al, 2011). TY0832 (MH1 ΔabpA::kan) and TY0833 (MH1 ΔabpB::kan) were constructed by GT7-mediated transduction of a kanamycin-resistance marker from strains JW2609 (BW25113 ΔyfjL::kan) and JW2608 (BW25113 ΔyfjK::kan), which were provided by the National BioResource Project (NIG, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…TA systems are broadly conserved in plasmids and bacterial chromosomes (Gerdes et al, 2005), and are implicated in many physiological roles, such as plasmid maintenance (Ogura and Hiraga, 1983;Yarmolinsky, 1995), stress response (Gerdes et al, 2005;Wang et al, 2011), bacterial persistence against antibiotics (Maisonneuve et al, 2011(Maisonneuve et al, , 2013Amato et al, 2013;Germain et al, 2013) and biofilm formation Wang et al, 2011). We have demonstrated that the two toxins RnlA and LsoA in TA systems are activated after T4 phage infection and result in shutting off gene expression by rapidly degrading mRNAs to block T4 propagation (Kai et al, 1996;Yonesaki, 2005, 2012;Koga et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…After boiling the samples, bound proteins were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) [10% gel for full-length RNase E-FLAG, 12% gel for RNase E(1-598)-FLAG, or 15% gel for Srd-His and His-IscR] and electroblotted onto Immuno-Blot PVDF membrane (Bio-Rad). Western blot analysis was performed as previously described (Koga et al 2011). Pull-down and immunoprecipitation analyses were performed at least three times, and a representative result is shown in Figure 5.…”
Section: Determination Of the Deleted Region In The D(39-56) 6 Phagementioning
confidence: 99%
“…coli K-12 strains MH1 (sup 0 araD139 hsdR DlacX74 rpsL), TY0807 (MH1 araD + ) (Koga et al 2011), and YT10 (MH1 zce726::Tn10) were used as wild types. YT10 or YT20 (YT10 ams1) was constructed by T4 GT7 phage transduction (Wilson et al 1979) of the tetracycline-resistance marker from GW10 (Wachi et al 1997) or by GT7 phage transduction of the tetracycline-resistance marker together with a temperature-sensitive mutation of ams1 from GW20 (Wachi et al 1997).…”
Section: Phages and Bacterial Strainsmentioning
confidence: 99%